2014
DOI: 10.1515/jpm-2014-0010
|View full text |Cite
|
Sign up to set email alerts
|

The value of lipopolysaccharide binding protein for diagnosis of late-onset neonatal sepsis in very low birth weight infants

Abstract: Serum LBP measurement may be useful as an additional tool in the evaluation of suspected LONS in VLBW infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…[1921] Currently, sCD14-ST level has been reported as an index for diagnosis and evaluation of hematosepsis in the infant with a low birth weight. [22] As there are only a few infants with a low birth weight among the subjects of this study, the above-mentioned report is not supported and further research on a large quantity of samples collected from infants with different birth weights is yet to be conducted.…”
Section: Discussionmentioning
confidence: 82%
“…[1921] Currently, sCD14-ST level has been reported as an index for diagnosis and evaluation of hematosepsis in the infant with a low birth weight. [22] As there are only a few infants with a low birth weight among the subjects of this study, the above-mentioned report is not supported and further research on a large quantity of samples collected from infants with different birth weights is yet to be conducted.…”
Section: Discussionmentioning
confidence: 82%
“…In humans, LBP triggers a dynamic endotoxin (such as LPS) transfer cascade by binding and transferring LPS to CD14, which transfer LPS to TLR4-MD-2 receptors on immune cells; LBP thereby concentrates LPS at the cell membrane of immune cells to stimulate an inflammatory response [40]. LBP also recognizes pathogens such as spirochaeta, mycobacteria, gram-positive bacteria and mycoplasma [41]. LBP binds pro-inflammatory constituents of both Gram positive and Gram negative bacteria [42], making it a more general marker of, bacterial exposures than LPS that stems only from Gram negative bacteria [38].…”
Section: Discussionmentioning
confidence: 99%
“…16 However, owing to the limitations of currently available biomarkers, such as CRP and PCT, 4 further efforts are needed to identify the novel biomarkers of infection. Previous studies have demonstrated the utility of LBP as a predictor of infection in patients with febrile neutropenia, 17 and of bacteraemia in children with community-acquired infection 1 and for diagnosing of late-onset neonatal sepsis 18,19 and febrile urinary tract infection in children. 20 In this study, we have analysed the value of LBP, measured on admission, for diagnosis of sepsis in patients admitted to the ED with suspected infection, compared with CRP and PCT.…”
Section: Discussionmentioning
confidence: 99%